No Evidence That Abstract Structure Learning Disrupts Novel-Event Learning in 8- to 11-Month-Olds - Wu, Rachel; Qian, Ting; Aslin, Richard N. (Frontiers in Psychology, 2019)
Although infants acquire specific information (e.g., motion of a specific toy) and abstract information (e.g., likelihood of events repeating), it is unclear whether extraction of abstract information interferes with specific learning. In the present study, eight- to 11-month-old infants were shown four audio-visual movies, either with a mixed or uniform presentation structure. Learning of abstract information was operationally defined as the looking time to changes in presentation structure of the movies (mixed vs. uniform blocks), and learning of specific information was defined as the looking time to changes in content in the four movies (object properties and identities). We not only found evidence of both specific and abstract learning, but more importantly that extraction of the presentation structure (i.e., abstract learning) did not disrupt specific learning of the events. We discuss the implications of the costs and benefits of the interaction between abstract and specific learning for infants.